Advanced Open Source Simulator: NS-3 - Jha, Rakesh Kumar; Kharga, Pooja (International Journal of Computer Sciences and Engineering, 2025)
in the current scenario various network simulators are available like OPNET, QualNet etc but all these software are commercial that means for using mentioned software, first one has to get licence. Therefore we focus on open source simulator (NS2 and NS3) that is open for everyone. This paper presents guideline for understanding the NS3 (Network Simulation Tool). NS3 focuses on improvement of software integrations, core architecture, models and educational components of NS2. This paper deals with basic idea about the simulator tool, installation procedure and how to design a network using it. In this paper Solution for common error occurred during installation of simulator and running a network is also provided. The purpose of this paper is to make network’s user familiar with the NS3 and its GUI (NetAnim).